Peningkatan Kemampuan Membaca Permulaan Melalui Media Papan Magnetik pada Murid dengan Gangguan Spektrum Autisme - Riska Aliyah Amatullah; Rahmahtrisilvia Rahmahtrisilvia; Marlina Marlina; Yosa Yulia Nasri (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Early reading is one of the fundamental skills that students with Autism Spectrum Disorder (ASD) need to develop in order to support their academic learning. However, some students with ASD continue to experience difficulties in reading meaningful simple words. This study aimed to examine the effectiveness of magnetic board media in improving the early reading ability of a first-grade student with ASD at SLB TIJI Padang. A quantitative approach was employed using an experimental method with a Single Subject Research A-B-A design. Data were collected through early reading tests administered during each session and analyzed using visual analysis presented in graphical form. The study consisted of 12 sessions, including the (A1), the (B), and the (A2). The results demonstrated a significant improvement in the student's early reading ability after the implementation of the magnetic board media. The mean score increased from 30 during the (A1) to 76.6 in the (B), and further reached 100 in the (A2). Within-condition analysis showed that the data trend shifted from stable to increasing and returned to a stable pattern in the final phase. In addition, the between-condition analysis indicated a positive level change with a low percentage of overlapping data. These findings suggest that magnetic board media are effective in improving the early reading ability of a first-grade student with ASD at SLB TIJI Padang.